UPAYA MENINGKATKAN AKTIFITAS DAN HASIL BELAJAR MATA PELAJARAN SIMULASI DIGITAL DENGAN METODE PEMBELAJARAN EXPLICIT INSTRUCTION PADA SISWA KELAS X JURUSAN AKUNTANSI 5 DI SMK NEGERI 1 KOTA SOLOK - Munas Munas (PAKAR Pendidikan, 2018)
The aim of the class room research was to find out activity and learning achievement can increase to use Explicit Instruction method. The population of this research was all of 36 student in class X AK-5 Senior High School Solok City. All student is population of this research by using total sampling technique. The data were analyzed through percentace. It was found that activity and learning achievement can increase to use use Explicit Instruction method.